2021
DOI: 10.3389/fpsyt.2021.622181
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Probiotic, Prebiotic, and Synbiotic Supplementation to Improve Perinatal Mental Health in Mothers: A Systematic Review and Meta-Analysis

Abstract: Introduction: There is an emerging interest in modulating the gut microbiota to target the gut-brain axis and improve maternal mental health in the perinatal period. This systematic review evaluated the effectiveness of prebiotics, probiotics, and synbiotics supplementation during pregnancy to reduce the risk of maternal mental health problems in the perinatal period.Methods: Electronic biomedical databases and clinical trial registries were searched from database inception through August 2020 to identify rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…A similar systematic review and meta-analysis by Desai and co-authors [ 9 ] focused on the effectiveness of probiotic, prebiotic and synbiotic administration on perinatal maternal mental health; however, it focused only on supplementation during pregnancy. It is well known that probiotic supplementation of mothers during breastfeeding or direct supplementation to the infant has several benefits for the infant, including developing a healthy microbiome, reduction in colic and regurgitation, the development of a healthy immune system, and reduction in the risk of atopic eczema [ 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A similar systematic review and meta-analysis by Desai and co-authors [ 9 ] focused on the effectiveness of probiotic, prebiotic and synbiotic administration on perinatal maternal mental health; however, it focused only on supplementation during pregnancy. It is well known that probiotic supplementation of mothers during breastfeeding or direct supplementation to the infant has several benefits for the infant, including developing a healthy microbiome, reduction in colic and regurgitation, the development of a healthy immune system, and reduction in the risk of atopic eczema [ 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the maternal and child’s microbial communities may be an important missing component in mother-infant attachment-based therapies during the treatment of perinatal depression [ 8 ]. One approach to improving maternal mental health in the perinatal period is targeting the gut-brain axis by modulating the gut microbiota [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an animal model, consumption of probiotics concomitant with an HFD started before pregnancy and continued until lactation was able to protect mice offspring against metabolic disturbances compared to offspring of dams on HFD alone (Guo et al, 2018). On the other hand, its effect in pregnant women is controversial since promising literature (Desai et al, 2021) contrasts with evidence such as a randomized clinical trial that found no benefits with Lactobacillus rhamnosus and Bifidobacterium lactis supplementation in obese pregnant women regarding depression and well-being (Dawe et al, 2020). Therefore, future studies are needed to robustly assert whether probiotic supplementation during pregnancy would be useful to prevent the development of mood disorders such as depression and anxiety in the progeny.…”
Section: The Gut-brain Axis During Fetal Developmentmentioning
confidence: 99%